PRISM (Program of Resources, Information and Support for Mothers) Protocol for a community-randomised trial [ISRCTN03464021] - Gunn Jane; Watson Lyndsey; Brown Stephanie; Small Rhonda; Lumley Judith; Mitchell Creina; Dawson Wendy (BMC, 2003)
Abstract Background In the year after birth one in six women has a depressive illness, and 30% are still depressed, or depressed again, when their child is 2 years old, 94% experience at least one major health problem (e.g. back pain, perineal pain, mastitis, urinary or faecal incontinence), 26% experience sexual problems and almost 20% have relationship problems with partners. Women with depression report less practical and emotional support from partners, less social support overall, more negative life events, and poorer physical health. Their perceptions of factors contributing to depression are lack of support, isolation, exhaustion and physical health problems. Fewer than one in three affected women seek help in primary care despite frequent contacts. Methods/Design PRISM aims to reduce depression and physical health problems of recent mothers through primary care strategies to increase practitioners' response to these issues, and through community-based strategies to develop broader family and community supports for recent mothers. Eligible local governments will be recruited and randomised to intervention or comparison arms, after stratification (urban/rural, size, birth numbers, extent of community activity), avoiding contiguous boundaries. Maternal depression and physical health will be measured six months after birth, in a one year cohort of mothers, in intervention and comparison communities. The sample size to detect a 20% relative reduction in depression, adjusting for cluster sampling, and estimating a population response fraction of 67% is 5740 × 2. Analysis of the physical and mental health outcomes, by intention to treat, will adjust for the correlated structure of the data.